Question
Asked Dec 19, 2019
16 views

Expand the binomial. (3x − y2)5

check_circle

Expert Answer

Step 1

To expand

help_outline

Image Transcriptionclose

(3x– y°)'

fullscreen
Step 2

Apply binomial theorem,

help_outline

Image Transcriptionclose

(a+b)" =E i=0 Here, a = 3x, b= -y²,n=5

fullscreen
Step 3

Then

...
help_outline

Image Transcriptionclose

(3x– r') =} |(3x)*"(-') (5-1) i=0 5! 5! ;(3x)'(-y²)". 0!(5– 0)! 1!(5-1): (3x)"(-y²)'+ 2!(5- 2)! 5! 21(5-2) (3x)"(-y²)* 1!(5 – 1)! 5! (3x)*(-y*)' + 4!(5– 4)! 5! 41(5 – 4)r (3.x)"(-3r²)* + 5!(5-5)! 5! 3!(5– 3)! Simplifying, we get = 243x – 405x*y² +270x²y* – 90x²y° +15xy® – yº S1(5-s5) (3x)'(-p²)'

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Exponents